2021
DOI: 10.3390/pr9040586
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of Olive Fruit Temperature before Grinding for Olive Oil Extraction. Experimental Study and Pilot Plant Trials

Abstract: Harvesting at high temperatures and bulk transport can negatively influence the quality of olives and lead to undesirable alterations in the extracted oil. Cooling the fruit in the field would be the most logical solution, but it means that the olives arrive too cold at the mill for immediate processing. In this work, the use of warm water in the washing tub to warm up the fruit before grinding instead of flash heat treatment on the paste was assessed in two experiments. In the first one, at the laboratory lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The feasibility of warm-up olives during their immersion in the washing tub might be an economic alternative [144]. Experiments at the laboratory as well as pilot-plant level demonstrated that an immersion time between 15 and 20 s in water at 35-40 • C suffice to warm-up olives at 10 • C to the desired 27 • C. It was further demonstrated that the temperature of the paste when entering the malaxer, could be easily monitored with a thermostat and adjusted by turning the electric heaters in the washing tub on and off.…”
Section: Adjusting To Desired Preprocessing Temperaturementioning
confidence: 99%
“…The feasibility of warm-up olives during their immersion in the washing tub might be an economic alternative [144]. Experiments at the laboratory as well as pilot-plant level demonstrated that an immersion time between 15 and 20 s in water at 35-40 • C suffice to warm-up olives at 10 • C to the desired 27 • C. It was further demonstrated that the temperature of the paste when entering the malaxer, could be easily monitored with a thermostat and adjusted by turning the electric heaters in the washing tub on and off.…”
Section: Adjusting To Desired Preprocessing Temperaturementioning
confidence: 99%
“…The Sono-Heat-Exchanger is equipped with an inner part that consists of a highly efficient spiral heat exchanger able to modulate the olive paste temperature (fast heating up or fast cooling of olive paste) simultaneously with the sonication treatment, adapting the results to the needs of olive millers [30].…”
Section: Thermal Effectmentioning
confidence: 99%
“…The biometrical characteristics of olives ('Picual' cv.) used in another experiment were used to calculate the air volume (V air ) in 1 m 3 [28,29]. The mean weight was 4.4 g and the volume, calculated after measuring the width and height and assuming the volume to be a prolate spheroid, was 4.14 cm 3 .…”
Section: Simulation Modelmentioning
confidence: 99%